Negative spin Hall magnetoresistance of normal metal/ferromagnet bilayers - Kang, Min-Gu; Go, Gyungchoon; Kim, Kyoung-Whan; Choi, Jong-Guk; Park, Byong-Guk; Lee, Kyung-Jin (Nature communications, 2020)
Interconversion between charge and spin through spin-orbit coupling lies at the heart of condensed-matter physics. In normal metal/ferromagnet bilayers, a concerted action of the interconversions, the spin Hall effect and its inverse effect of normal metals, results in spin Hall magnetoresistance, whose sign is always positive regardless of the sign of spin Hall conductivity of normal metals. Here we report that the spin Hall magnetoresistance of Ta/NiFe bilayers is negative, necessitating an additional interconversion process. Our theory shows that the interconversion owing to interfacial spin-orbit coupling at normal metal/ferromagnet interfaces can give rise to negative spin Hall magnetoresistance. Given that recent studies found the conversion from charge currents to spin currents at normal metal/ferromagnet interfaces, our work provides a missing proof of its reciprocal spin-current-to-charge-current conversion at same interface. Our result suggests that interfacial spin-orbit coupling effect can dominate over bulk effects, thereby demanding interface engineering for advanced spintronics devices. In normal metal/ferromagnet bilayers, the spin Hall magnetoresistance originating from the spin Hall effect of normal metal possesses positive sign regardless of the sign of spin Hall conductivity of normal metal. Here, the authors report negative spin Hall magnetoresistance of Ta/NiFe bilayers due to interfacial spin orbit coupling at interfaces.